2021
DOI: 10.48550/arxiv.2107.13550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mimetic Euler-Heisenberg theory, charged solutions and multi-horizon black holes

G. G. L. Nashed,
Shin'ichi Nojiri

Abstract: We construct several new classes of black hole (BH) solutions in the context of the mimetic Euler-Heisenberg theory. We separately derive three differently charged BH solutions and their relevant mimetic forms. We show that the asymptotic form of all BH solutions behaves like a flat spacetime. These BHs, either with/without cosmological constant, have the non constant Ricci scalar, due to the contribution of the Euler-Heisenberg parameter, which means that they are not solution to standard or mimetic f (R) gra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 88 publications
(160 reference statements)
0
3
0
Order By: Relevance
“…It has also been shown that this theory can explain the flat rotation curves of spiral galaxies without needing to particles DM [10,11]. Mimetic theory of gravity has arisen a lot of enthusiasm in the past few years both from the cosmological viewpoint [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] as well as black holes physics [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. The investigations on the mimetic theory of gravity were also generalized to f (R) gravity [51][52][53][54][55][56][57][5...…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that this theory can explain the flat rotation curves of spiral galaxies without needing to particles DM [10,11]. Mimetic theory of gravity has arisen a lot of enthusiasm in the past few years both from the cosmological viewpoint [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] as well as black holes physics [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. The investigations on the mimetic theory of gravity were also generalized to f (R) gravity [51][52][53][54][55][56][57][5...…”
Section: Introductionmentioning
confidence: 99%
“…A study of the thermodynamics of these black holes was performed in [15,16], while the stability of these black holes, calculating the quasinormal modes, was studied in [17]. Rotating black holes were found in [18,19], while the Euler-Heisenberg theory in modified gravity theories in [20][21][22] was studied and black hole solutions were analyzed.…”
mentioning
confidence: 99%
“…Nevertheless, mimetic gravity can be extended in many ways, interpreted as a modification of gravity (for a review see [76]). Since mimetic modified gravity have many interesting applications at the cosmological framework (among them the ability to alleviate the cosmological tensions [77], and to track possible quantum-related defects [78]), an amount of research has been devoted to the investigation of the spherically symmetric solutions too [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95].…”
mentioning
confidence: 99%